MENINGKATKAN KEMAMPUAN MENULIS TEKS ANEKDOT MELALUI GENDRE BASSED APPROACH PADA SISWA KELAS VIII SMP NEGERI SATU ATAP BOBALE. - Meita Meriske Antonia; Sarmina Ati (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2024)
This study aims to improve the ability to write anecdotal texts of eighth grade students of SMP Negeri Satu Atap Bobale. by applying a genre-based approach. The research model used is Classroom Action Research (CAR). The procedure for implementing actions and implementing actions at the research location is divided into two cycles. Each cycle is carried out three times. The success achieved by students in this study is seen from the changes towards the better and the increase in learning activities and results in the practice of writing anecdotal texts. The results of the study show that. First, the increase in the genre-based approach is able to improve the quality of the learning process of writing anecdotal texts. There is an increase in the process in the aspects of learning situations, student focus, and activeness, making positive changes so that learning to write anecdotal texts is more interesting and enjoyable. Second, learning to write anecdotal texts with a genre-based approach can improve the results of anecdotal text writing skills before being given Action is 64.53 while after being given action in cycle II the average score becomes 85.00. This shows an increase of 20.47. Overall, at the end of cycle II, all aspects and criteria for writing anecdotal texts experienced significant improvement. Based on the research results above, it is known that the use of the genre-based approach was successful and could improve the anecdotal text writing skills of eighth-grade students at SMP Negeri Satu Atap Bobale.